The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1993
DOI: 10.1073/pnas.90.15.7371
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and transmission of the Lyme disease spirochete from the southeastern United States.

Abstract: The isolation of the Lyme disease spirochete (Borrelia burgdorferi) from the southeastern United States is reported. Three isolates, two from cotton mice (Peromyscus gossypinus) and one from the black-legged tick (Ixodes scapularis), were recovered from Sapelo Island, Georgia, in July and September 1991. The spirochetes were characterized by indirect fluorescent antibody assay using a battery of five monoclonal antibodies, by sodium dodecyl sulfate/polyacrylamide gel electrophoresis (SDS/PAGE) of whole cell ly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
41
0
1

Year Published

1996
1996
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(45 citation statements)
references
References 31 publications
3
41
0
1
Order By: Relevance
“…Vector competency studies have concluded repeatedly that B. burgdorferi is unlikely to be transmitted by A. americanum (10)(11)(12)(13)(14)(15)(16), and a potent borreliacidal agent has been identified in A. americanum saliva (17,18). From 1997 to 2010, the Department of Defense (DOD) Human Tick Test Kit Program (HTTKP), a tick identification and PCR testing service provided by the U.S. Army Public Health Command (USAPHC) for DOD personnel and dependents, tested 22,565 A. americanum ticks (21,245 adults and nymphs removed from humans, and 1,320 field-collected larvae) for borrelial agents of Lyme-like diseases using a series of nested-and real-time PCR assays.…”
mentioning
confidence: 99%
“…Vector competency studies have concluded repeatedly that B. burgdorferi is unlikely to be transmitted by A. americanum (10)(11)(12)(13)(14)(15)(16), and a potent borreliacidal agent has been identified in A. americanum saliva (17,18). From 1997 to 2010, the Department of Defense (DOD) Human Tick Test Kit Program (HTTKP), a tick identification and PCR testing service provided by the U.S. Army Public Health Command (USAPHC) for DOD personnel and dependents, tested 22,565 A. americanum ticks (21,245 adults and nymphs removed from humans, and 1,320 field-collected larvae) for borrelial agents of Lyme-like diseases using a series of nested-and real-time PCR assays.…”
mentioning
confidence: 99%
“…At first, analysis targeted B. burgdorferi, because A. americanum was suspected as a vector of Lyme disease. However, vector competency studies indicated that B. burgdorferi is rarely transmitted by A. americanum (19,21,22,25,26,30,32) b Corresponds to sequence data generated in this study, under GenBank accession numbers AY237656, AY237667, AY237671, AY237677, AY237678, AY237679, and AY237707.…”
Section: Discussionmentioning
confidence: 99%
“…3 In the southeastern states, an anomalous situation exists where Ixodes scapularis is widespread but is rarely found infected with B. burgdorferi or attaching to humans. 4 Although B. burgdorferi isolations from humans are made, 5 such isolations are uncommon in this region, although a clinically similar disease, termed Southern Tick-Associated Rash Illness (STARI), is not unusual and is associated with the bites of Amblyomma americanum ticks. 6 Lyme disease in the western United States is both less common and ecologically more complex than described on the East Coast.…”
Section: Introductionmentioning
confidence: 99%